Symptomatic Intracranial Hypertension Secondary to Superior Vena Cava Thrombosis as the First Manifestation of Behçet’s Disease: ATYPICAL FIRST MANIFESTATION OF BEHCET’S - Sadry, Payam; Magsi, Rayan; Ahmed, Maahum; Amsdell, Jennifer; Derani, Talal; Mahfooz, Naeem; Sheikh, Ajaz (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Introduction: Behçet’s disease (BD) is a rare inflammatory autoimmune disorder characterized by recurrent oral and genital ulcers, uveitis, and other systemic manifestations. Reported neurological manifestations of BD include meningoencephalitis, cerebral venous thrombosis, intracranial hypertension (ICH), and cranial nerve palsies. Involvement of the superior vena cava (SVC) is rare but should be considered in patients with BD with suspected ICH. Case Report: A 32-year-old man presented with ICH as the initial manifestation of BD. He presented with a one-week history of facial and neck edema, headache, and blurry vision, followed by fever, sore throat, and oral blisters a few days later. Lumbar puncture (LP) was performed, and opening pressure was found to be elevated at >50 cmH2O and closing pressure of 36 cmH2O. The work-up included a chest CT, which identified thrombosis of the SVC extending into the brachiocephalic veins, and blood work which revealed elevated inflammatory markers. Further probing revealed a history of genital ulcers and a family history of a cousin with BD. The patient underwent mechanical thrombectomy and was treated with oral prednisone with symptom resolution. Conclusion: BD has a wide spectrum of symptomology and may present without common manifestations, making it challenging to diagnose. The aim of our report was to emphasize the importance exploring the rarer vascular, neurological, and cardiac symptoms of BD in order to avoid potentially dangerous sequala. A system approach may be necessary to diagnose and optimally treat these patients.